The physiological composition of elite judo players - Pulkkinen, W. (2002)
(i) An Analysis of Judo Mechanics and the Competitive Judo Match (ii) The Physical Basis of Competitive Judo: Match Dynamics (iii) Physiological Profiles of Elite Judo Athletes a) Percent Body Fat of Elite Judo Players b) Fibre Type Composition of Elite Judo Players c) Aerobic Requirements of the Elite Judo Player Practical applications to the coach and sport scientist involve an understanding that aerobic performance and conditioning is not paramount in the physical development of world class judo athletes. Judo performance does require a good aerobic base or aerobic working capacity, and this can be developed through the nature of a typical competition practice. Judo practice would be a means of improving general conditioning, whereas running would be a means of enhancing general conditioning (Matsumoto et al, 1978). The very nature of judo training would involve athletes performing at or above 75 % of their individual heart rate maximums for a sustained period of 30-40 minutes during free practice sparring or "randori" (Kaneko et al, 1978). Perhaps the greatest benefit of aerobic training is the judo player's ability to operate at a high percent of their individual aerobic capacity. Research has indicated that trained aerobic individuals can work at 75-85% of their aerobic power before experiencing fatigue (NCCP, 1990). Callister et al (1991) reported that ventilatory thresholds of judo athletes were high, and that lactate levels following treadmill testing were low. This was most likely due to a reflection of the large quantity of high intensity training performed by elite judo players. This introduces the concept of anaerobic threshold training (AnT), or the point at which lactate production exceeds its removal during exercise (Astrand and Rodahl, 1986). Due to the high intensity nature of the sport, judo players repeatedly operate at or above the AnT throughout the course of training and competition. As a result, training should involve competitive situations, which would require the athlete to attain their individual AnT for a brief period. The corresponding physiological and biochemical adaptations would result in the athlete being able to perform at a higher percent of his VO2, and thus perform with more intensity during the match, in addition to being able to recover quicker between each high intensity match. The judo athlete should be tested regularly throughout the year to determine if the individual's VO2 score is at a comparable level to other world class judo athletes. Scores should be at a minimum of 55-60 ml kg-1 min-1, and if not, focus on the early stages of training should be to ensure that this score is acquired. Successful participation in judo competitions is technically mastery supported with above average endurance capacities (Little, 1991). This is typically done early in the athlete's career prior to world level competition and often is a result or by product of regular repeated practices over several years.